Highway interchange simulation - Mohamed Balrwin, Rafeg Ali (2008)
This paper presents a real case study endeavor to apply highway interchange simulation distribution of vehicle movement by using modeling to review, assess, and improve the current traffic practices in Malaysia. First, building the implementation process diagram for a traffic modeling simulation and determine the flow sequence with vehicles quantity. Secondly, Time measurement for implementation processes and monitor, control the traffic flow which presented in three interchanges. Finally, the interchanges are presented from (Skudai to Johor Bahru) that needed to finish the overall traffic cycle time. Furthermore, the important parameters to build the simulation processes are vehicles quantity, lanes number and time factor. Therefore, the case study data were obtained in two stages: (i) during the morning period and (ii) during the evening period. Consequently, the data were collected with observation. The importance of traffic work flow in a developing country was clarified as time-based analysis, in which the completion cycle time of the highway project in the overall duration to vehicles were calculated separately by using Witness (2001) software. As a result the output is depended on the quantity of vehicles for each interchanges and time period by applying the simulation.